Constraining Lorentz invariance violation from the continuous spectra of short gamma-ray bursts - 常哲 李昕 林海南 桑语 王平 王赛 (Chinese physics C, 2016)
In some quantum gravity theories, a foamy structure of space-time may lead to Lorentz invariance violation（LIV）. As the most energetic explosions in the Universe, gamma-ray bursts（GRBs） provide an effect way to probe quantum gravity effects. In this paper, we use the continuous spectra of 20 short GRBs detected by the Swift satellite to give a conservative lower limit of quantum gravity energy scale MQG. Due to the LIV effect, photons with different energy have different velocities. This will lead to the delayed arrival of high energy photons relative to low energy ones. Based on the fact that the LIV-induced time delay cannot be longer than the duration of a GRB,we present the most conservative estimate of the quantum gravity energy scales from 20 short GRBs. The strictest constraint, M_（QG） 〉 5.05 × 10~（14） GeV in the linearly corrected case, is from GRB 140622 A. Our constraint on MQG,although not as tight as previous results, is the safest and most reliable so far.